How to read church history ; v. 2. - Comby, Jean; MacCulloch, Diarmaid; Lydamore, Margaret; Bowden, John; Piorkowski, Liliane; Bowden, Rachel (London, UK SCM, 1989)
Contents : v. 2 : From the reformation to the present day. Includes bibliographical references.
First published : Pour lire L'Histoire de L'Eglise Tome 2, Paris : Les Editions du Cerf, 1986
Keywords: Reformation -- study and teaching; Church history -- modern period, 1500- -- study and teaching